2016
DOI: 10.1016/j.fertnstert.2016.07.1121
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and body mass in women with polycystic ovary syndrome identified in referral versus unselected populations: systematic review and meta-analysis

Abstract: The prevalence of more complete phenotypes in PCOS and mean BMI were higher in subjects identified in referral versus unselected populations, suggesting the presence of significant referral bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 61 publications
1
78
0
17
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17] For some women, such as those with severe hyperandrogenism, early diagnosis and management of PCOS could arguably slow progression of comorbidities and prevent long term harms by prompting early intervention. A PCOS label might, for example, help women undergo regular screening for comorbidities and make dietary and lifestyle changes, such as losing weight and reducing risk of diabetes or cardiovascular disease (table 3⇓).…”
Section: Rationale For Changementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] For some women, such as those with severe hyperandrogenism, early diagnosis and management of PCOS could arguably slow progression of comorbidities and prevent long term harms by prompting early intervention. A PCOS label might, for example, help women undergo regular screening for comorbidities and make dietary and lifestyle changes, such as losing weight and reducing risk of diabetes or cardiovascular disease (table 3⇓).…”
Section: Rationale For Changementioning
confidence: 99%
“…It has been shown that PCOS patients from referral population have a greater mean BMI and higher prevalence of obesity compared to women with PCOS diagnosed in the medically unselected population. [7][8][9][10][11][12] The evidence that obesity is associated with higher prevalence of PCOS is conflicting too. Data from some retrospective and longitudinal observational studies have suggested the higher incidence of PCOS among obese women, but it was not supported by data obtained in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…10 At the same time some authors reported that the prevalence of metabolic syndrome does not differ in obese vs non-obese women with PCOS. This may be explained by the heterogeneity of the groups of infertile women due to different causes of infertility, PCOS phenotype and racial differences.…”
mentioning
confidence: 99%
“…Although it is most clinically apparent among women of reproductive age, PCOS can be symptomatic in pre-adolescent and menopausal women, and potentially even in men. 3,4 PCOS is also associated with an increased risk of endometrial and possibly ovarian carcinoma. In addition to hyperandrogenic dermatologic symptoms (acne, alopecia, and hirsutism), PCOS is associated with impaired reproduction and obstetric outcomes.…”
mentioning
confidence: 99%
“…In 1990, the relatively strict US National Institutes of Health (NIH) criterion categorized two phenotypes of PCOS: phenotype A, comprising oligo-anovulation, hyperandrogenism, and PCOM; and phenotype B, comprising oligo-anovulation and hyperandrogenism. 4 Consequently, to gain the most accurate understanding of the prevalence of PCOS, epidemiologic studies of unselected or unbiased populations must be undertaken. 10 There is strong evidence that the features of PCOS identified among clinically referred patients are more severe than the phenotypes of PCOS identified in studies of medically unbiased (unselected) populations.…”
mentioning
confidence: 99%